Spatio-temporal evolution of the crustal uplift in Eastern NE China: constraint from detrital zircon ages of Late Mesozoic clastic rocks in the Boli Basin - He, Song; Cheng, Hong; Li, Shuang-Qing; Cao, Cong; He, Jun; Chen, Fukun (Minerals, 2022)
Detrital zircon of clastic rocks has been widely recognized as a powerful tool for the study of crustal uplift, which is of great significance for understanding multi-sphere interaction. However, young detrital zircons can only roughly constrain the depositional time of the strata, and commonly used zircon age probability density and kernel density estimations cannot provide sufficient evidence to reveal spatio-temporal differences in tectonic uplift. The basins developed in active continental margins usually contain abundant magmatic rocks, which can provide insights into basin evolution and crustal deformation when combined with sedimentary characteristics. In this study, we report detrital zircon ages of Late Mesozoic clastic rocks from the Boli Basin, being part of the Great Sanjiang Basin Group in eastern NE China, which is strongly affected by the Paleo-Pacific subduction. In conjunction with the age data of coeval magmatic rocks and potential sedimentary sources of basement rocks adjacent to the basin, the geochronologic results of this study provide solid evidence for the formation of the Boli Basin and the spatio-temporal evolution of the crustal uplift in northeastern China. The Boli Basin went through multi-phase tectonic evolution of syn-rift and post-rift stages, based on the zircon age data of clastic and igneous rocks. When the geographical distribution characteristics of potential sedimentary sources and their percentages of contribution are taken into account, two stages of eastward migration of the crustal uplift and two episodes of basin destruction caused by the tectonic extension and subsequent compression can be proposed for the Boli Basin. These processes were caused successively by the rolling back of the subducted Paleo-Pacific slab, the docking of the Okhotomorsk block along the eastern continental margin of East Asia, and the transition of the subduction zone by the collision of the Okhotomorsk block.
Gesehen am 17.11.2022